INNOVATION THE CLUSTER APPROACH ON THE BASIS OF IMPROVEMENT OF PROFESSIONAL SKILLS OF FUTURE TEACHERS - Shamshodjon Boltayev, (Educational Research in Universal Sciences, 2023)
This article outlines the inter-clonal sectors interaction school of pedagogical experience as a laboratory for the innovative cluster approach by increasing the basi. Also, physical culture and development of an innovative cluster is not the only format aimed at the teaching of the educational direction of the school between tea and munching aimed at increasing general second increasing visionary, but also at developing the scientific and creative potential of students and the professional personnel from the point of view of region’s students need for the future.